Konsumsi zat gizi dan parameter lemak tubuh pada wanita umur lebih dari 40 tahun - Kadek Tresna Adhi; Ni Ketut Sutiari; Dinar SM Lubis; Ni Putu Widarini; I Gusti Ngurah Edi Putra (Jurnal Gizi Klinik Indonesia, 2020)
Food intake and body fat parameter among women older than 40 years old in DenpasarBackground: The prevalence of obesity in Indonesia tends to increase, particularly among women older than 40 years old.Objective: This study aimed to identify the associations between nutrient consumption and parameters of body fat among women in Denpasar.Methods: This was an observational analytic study with a cross-sectional approach. The population was women aged older than 40 years old in Denpasar with sampled population were members Dharma Wanita PDAM Kota Denpasar. Eighty out of 200 women were selected through systematic random sampling method. Variables collected in this study included women’s characteristics, nutrient consumption, and body fat parameters: body mass index (BMI), waist circumference (WC), and waist to hip ratio (WHR). Analysis of the relationship between nutrient consumption and body fat parameters using the Spearman Rank correlation.Results: This study found that the majority aged 41-50 years (83.8%), were Balinese  (95.0%), have married  (98.8%), did not use contraception (65.0%), completed higher education (63.8%), worked in informal sector (60.0%), had low income (65.0%), had no history of obesity (80.0%) and no family with degenerative diseases (73.8%). Based on the body fat parameters, most of the women were obese based on BMI (52.5%), WC (70.0%), and WHR (57.5%) categories. There was a significant association between fiber consumption and waist circumference (p=0.021).Conclusions: There was an association between fiber consumption and waist circumference, thus having a balanced and varied diet is recommended to prevent obesity and reduce risk factors for degenerative diseases.